Rare Metastasis of Primary Pancreatic Adenocarcinoma to the Bladder. Issue 1 (2018) - Shah, Anup; Korrapati, Praneet; Siegel, Jerome; Kasmin, Franklin
ABSTRACT : N/A: Pancreatic cancer commonly metastasizes to the liver, lungs, stomach, bone, and bowel, but rarely does it spread to the bladder. We describe a case of a 66‐year‐old woman with diabetes mellitus who presented with abnormal liver function laboratory tests, abdominal discomfort, unintentional weight loss, and no urinary symptoms. Abdominal CT revealed a pancreatic and bladder mass. Pathology of the bladder mass confirmed metastatic adenocarcinoma of pancreaticobiliary origin. To our knowledge, this is only the third case of metastatic pancreatic cancer spreading to the bladder since 1953.